Identifier Handling in Information Systems: The Case of University Student Registration Systems in Thailand - Boonam, Pattana; Chittayasothorn, Suphamit (My University, 2024)
In modern information systems, identifiers play important roles in information systems and databases. An information system can be regarded as a simulated computerized system. Each object instance or entity instance represents a real-world object. There must be a unique identifier or a key value which uniquely identifies each such object instance. One of the earliest applications in a university is the student registration system or students' record management system. These systems originated some decades ago using the old-style record-at-a-time languages and file-based technology. Instead of using the identifier concept, these systems employ the classifier concept which affects the functionality of the systems. This paper addresses the issues related to using identifiers as classifiers and proposes a solution. Case studies from several universities in Thailand are also presented.
Keywords: Identifiers; Information Systems; Meaningful keys; Student Registration Databases